Imre Lakatos Research Programme Methodology Application in the Curriculum of Islamic Education in Madrasah - Lely Nurarifah; Paryanto (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
Imre Lakatos's thoughts need to be developed in Islamic education, especially in schools with a larger portion of Islamic education when compared to public schools. This study aims to explain Imre Lakatos's thinking, which is often referred to as the research program methodology, as well as to analyze the application of the Imre Lakatos research program methodology in the Islamic education curriculum in madrasas, taking into account the three elements of the research program proposed by Imre Lakatos. Three elements in the research program include hardcore, protective belt, and a series of theories. A literature study approach supports the qualitative method used in this research. Data sources used are relevant literature obtained from books and journal articles. The data collection technique used is documentation. The results of this study show that the Islamic education curriculum based on the Al-Qur'an and Hadith occupies the main core (hardcore) position. Meanwhile, the subjects of Al-Qur'an Hadith, Aqidah, Jurisprudence, and Islamic Cultural History became the protective belt.